Antioxidant system in rats' skeletal muscles and blood at hyperglycemia and the influence of zinc citrate - Слівінська, О. М.; Сеньків, О. М.; Іскра, Р. Я. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
Data about the influence of zinc citrate on indices of the antioxidant system in rats’ skeletal muscles and blood at experimental diabetes mellitus (EDM) are presented in the article. The decreased activity of antioxidant defense system enzymes and increased lipid hydroperoxides content in rats’ skeletal muscles and blood and MDA content in rats’ skeletal muscles at EDM were established, compared to the rats of the control group. At zinc citrate addition in doses of 20 and 50 mg Zn/kg of body weight to the diet of rats with experimentally induced diabetes we observed increased activity of investigated enzymes and decreased lipid hydroperoxides content in skeletal muscles and blood, and increase of reduced glutathione content in erythrocytes, which may indicate the activation of antioxidant processes and normalization of the physiological and biochemical state of rats’ organism under the action of zinc citrate.